Modeling circular inductors coupled to a semi-infinite magnetic medium considering the proximity effect. Issue 13 (2nd September 2017) - Gendron, Mathieu; Hazel, Bruce; Boudreault, Eric; Champliaud, Henri; Pham, Xuan-Tan
Abstract: This paper presents a simple 2D electromagnetic model that solves the high-frequency current distribution, considering the proximity effect, in a planar spiral coil above a linear conductive or non-conductive semi-infinite magnetic medium. The conductive regions are divided into axisymmetric elements in which the current is assumed constant. The current flowing in each element depends on its complex impedance and is computed by Kirchhoff's circuit law. To take the effect of the magnetic medium into account, a new set of mutual inductance formulas are presented. Those formulas are expressed in terms of elliptic integrals and the fast-converging arithmetic–geometric mean iteration of Gauss. The geometric mean distance method is used to deal with elements of arbitrarily shaped cross-section. Elliptic integrals are also used to express the magnetic flux density. The current distribution, the magnetic field and the equivalent impedance computed with the multifilament model agree well with the results obtained using commercial finite element software.